PENGARUH PEMANFAATAN E- LEARNING TERHADAP HASIL BELAJAR IPS PADA PESERTA DIDIK KELAS VIII SMP ISLAM BAWARI PONTIANAK - Fanni Yoga Pratama; Aminuyati Aminuyati; Hadi Wiyono (Universitas Tanjungpura, 2022)
This study aims to determine the effect of E-learning utilization on the learning outcomes of eighth grade students at SMP Islam Bawari Pontianak. The research method used is a quantitative approach with a descriptive form. The sample in this study was class VIII SMP Islam Bawari totaling 70 students using saturated sampling technique. The data collection tool uses a questionnaire that is about of E-learning utilization with 3 indicators : knowledge, the character of E-learning and the application of E-learning . And documentation techniques are used to retrieve learning outcomes. Based on data analysis, it shows that: 1) the use of E-learning for eighth grade students at SMP Islam Bawari Pontianak is in the medium category with a percentage yield of 74.3%. 2) the learning outcomes of eighth grade students at SMP Islam Bawari Pontianak have a percentage of 72.9% in the medium category. 3) Based on the analysis of the use of E-learning on learning outcomes, the regression coefficient results are 0.716 and the standard value of significance is 0.00 < 0.05. And the results of tcount > t table are 7.005 > 1.997.